Análise citotóxica e caracterização química de frações do extrato hidroalcoólico da semente de Euterpe Oleracea mart - Freitas, Dayanne da Silva (2016)
The Euterpe oleracea Mart seed. (Acai) has demonstrated different biological activities, such as antioxidant, anti-inflammatory, antihypertensive, antinociceptive and antineoplastic. In this new study, the aim was to analyze the antineoplastic activity of fractions derived from hydroalcoholic extract of Euterpe oleracea Mart. seed in cell line MCF-7, and to identify the compounds responsible for the antineoplastic action by mass spectrometry using electrospray ionization source, and a ciclotrônico analyzer coupled to a Fourier transform (ESI-FT-ICR MS). The MCF-7 cell line was treated with 10, 20, 40 and 60 μg L-1 with fractions hexane (FH), chloroform (FC) and ethyl acetate (FAE) of the hydroalcoholic extract acai seed for 24, 48 and 72 hours. After treatment the cell viability was measured using the assay with 3- (4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide (MTT) and the cell type of death was assessed using annexin - Iodide propidium (PI) assay. Data were analyzed statistically by analysis of variance (ANOVA) or Student's t test, us appropriate. It was observed that all the fractions caused significant reduction of cell viability of MCF-7, but the FAE was the most cytotoxic (p <0.001). In the test Annexin-PI, there was no significant labeling annexin but increased PI staining was significant (p <0.001). This study showed that the FAE was more effective in reducing cell viability, following necroptose mechanism in MCF-7 cell. The FAE is composed of epicatechin, proanthocyanidin A2 and trimeric and tetrameric procyanidins.